Nitrate concentrations and postharvest quality of green leafy vegetables in organic and conventional cropping systems, Selangor, Malaysia - Hamidon, Azimah (2015)
The unregulated application of nitrogen fertilizers would result in luxury uptake of nitrate concentration in leafy vegetables, leading to the conversion of nitrate to nitrite and eventually to carcinogenic nitrosamines during storage. The greenness of green leafy vegetables is the result of fertilizer application to specifically nitrogen fertilizer. In Malaysia, the grade of nitrogen in most organic fertilizers is not ensured, thus leading to over application of nitrogen to the vegetable crop per growing season. The objective of the first experiment was to determine the leaf nitrate, nitrite and chlorophyll contents, nitrate reductase activity and colour of selected vegetables (Amaranthus viridis, Brassica rapa, Lactuca sativa) from three organic (ORG1, ORG2 and ORG3) and three conventional (CONV1, CONV2 and CONV3) farms in Selangor. The experiment was conducted in a completely randomized design with five replications. The organic B. rapa and L. sativa vegetables contained higher nitrate content, 1659 and 1119 mg/kg fresh weight (FW), respectively, compared to those of conventional vegetables. The nitrate reductase (NR) activity in organic L. sativa leaves was 56% higher than conventional. The leaf colour of the organic and conventional vegetables was deep, grayish or pale green. This could resulted in 31.1% and 23.6% higher chlorophyll content in conventional A. viridis and L. sativa leaves was than organic vegetables leaves. High nitrate content is associated with dark leaf colour, as well as high chlorophyll content. Thus, the consumers' perception regarding dark green leafy vegetables as being related to freshness and high quality is doubtful. The second experiment was carried out to determine the effects of cropping systems (organic and conventional) and storage duration (0, 3, 6 and 9 days) on postharvest quality characteristics, antioxidant activity, chlorophyll content and nitrate and nitrite contents of A. viridis, B. rapa and L. sativa. The leafy vegetables used were selected from the cropping systems that produced the highest nitrate contents as determined in the first experiment. The experiment was conducted using the randomized complete block design, arranged in a factorial experiment, with five replications. The A. viridis, B. rapa and L. sativa from the two cropping systems showed 4.5 to 8% weight loss and decreased firmness by 33 to 45.6% during storage. The organic and conventional vegetables showed the colour changes from dark grayish, deep and pale green to bright grayish, grayish and yellowish dull green during storage. The colour changes were influenced by the degradation of chlorophyll content in A. viridis, B. rapa and L. sativa during storage. The NR activity of organic and conventional B. rapa and conventional A. viridis were 51 to 71% increased by storage day 3. The three organic and conventional leafy vegetables were 78 to 95.4% reduced in nitrate contents and 99% increased in nitrite content as storage days increased. It can be suggested that leafy vegetables, such as A. viridis, B. rapa and L. sativa, should not be kept under refrigerated (5 ºC) storage for more than 3 days. This is to prevent an increase in nitrite content, excessive water loss, firmness reduction, changes in total phenolic, ascorbic acid and antioxidant activity, and to maintain the postharvest quality of the vegetable. It is recommended that studies be carried out to determine the nitrate contents of other types of leafy vegetables grown under organic and conventional cropping systems. The soil nitrate contents where the vegetables are grown should also be determined. Future studies should be conducted to determine the optimum nitrogen requirement for leafy vegetables to prevent excess utilization of nitrogen fertilizers.